Policy Analysis of Principals' Competency in Primary Schools - Velerisa Febyola; Rizki Ananda; Alta Feros; Citra Wulandari (research, training and philanthropy institution Natural Aceh, 2023)
Education is one of the most important aspects of the continuity of human life. The role of school principals in educational institutions is crucial and is connected with implementing various elements in carrying out their duties. Various policies under the control of school principals determine the level of educational quality success, which also depends on the school principal's policies. Problems arise when it is known that several school principals throughout the provinces of Indonesia need more competence. The purpose of this research is to investigate the implementation of school principal competency policies in elementary schools. This article is written using a qualitative approach. The results show that a school principal must fulfil and possess comprehensive skills in competency policies, especially at the elementary school level. The school principal must first understand the job description based on competency standards. Each school has its unique vision and mission compared to other schools. The determination of the vision and mission is adjusted to the school principal's goals in directing the school towards specific areas driven and supported by the surrounding school environment factors. The conclusion drawn from the conducted research is that the school principal's competency policies include social competence, supervision, entrepreneurship, managerial skills, and personality.